The role of non formal education in transforming power relations and challenging gender : a critical case study of an alternative basic education programme in Alaba Kulito, Ethiopia - Garcia Piriz, Aranzazu (2010)
Top to bottom initiatives are being exported to developing countries with the same patterns and patriarchal structures that exist in the west. Since the 70´s and currently, non formal education (NFE) programmes are being used by International Agencies, NGOs and Governments to promote universal education and gender equality. These goals have been approached from different political discourses along time, making NFE an instrument characterised and defined in various ways. At present NFE appear as a mechanism in the Millennium Development Goals Report and in the Educational Policy in Ethiopia involving in theory the participation and empowerment of direct and indirect beneficiaries. In this context, this study looks at the power dynamics and gender relations that are generated in a NFE programme in Ethiopia specifically an Alternative Basic education centre, questioning the absence of theory in NFE programmes currently and its consequence of not approaching education as an empowerment element or pragmatic instrument to challenge the status quo. Through a gender analysis of various aspects of the concrete programme we arrive to the theoretical discourse that embraces this new era of post development. In addition, this paper carries out an analysis of how the patterns of traditional gender roles and power dynamics are systematically and institutionally repeated and not challenged through non formal education.